STRATEGI MARKETING PUBLIC RELATIONS DALAM MENINGKATKAN JUMLAH TAMU HOTEL PANTAI MARINA BENGKALIS - Maryam "; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Companies use promotions to convey expected messages to audiences and may influence public perceptions and actions. The function of Public Relations in achieving the company's goal is to increase the hotel guest's visit, a PR must have a Marketing Public Relations strategy as a priority plan to achieve the company's goals, one of which attracts customers to continue to use their services. Seeing the business competition in the field of hospitality makes the businessmen have to think hard to create the best Marketing Public Relations strategy in order to attract customers. It takes a marketing strategy to increase the guest's visit at the Marina Beach Hotel. From the data the researchers get in the field on pre-observation, the researcher is interested to conduct this research with the aim to see the marketing strategy of Public Relations used in improving the guest's visit at this hotel.This research is a descriptive research using qualitative approach as a tool of its analysis. This researcher informant is from Hotel Pantai Marina is Manager, Assistant Manager, Secretary HRD Hotel Marina Beach as well as hotel visitors as many as 8 people. Observation data collection techniques, interviews and documentation. Technique of data analysis writer use in this research is descriptive qualitative. The result of the research is Public Relations Marketing Strategy through Information in improving guest visit of Marina Bengkalis Beach Hotel done by giving information through media in the form of facebook, spreading a brochure or pamphlet installation, Marketing Public Relations strategy through public service in increasing guest visit Hotel Marina Bengkalis Beach done By providing good service and being hospitable, Marketing Public Relations Strategy through publication in improving the visit of Marina Bengkalis Beach Hotel is done by intensifying promotion in print media and social media, deploying special promos related products and services offered by the Hotel.